Diet variability among pre‐Dogon and early Dogon populations (Mali) from stable isotopes and dental diseases. Issue 2 (9th April 2019) - Dlamini, Nonhlanhla; Sealy, Judith; Mayor, Anne
Abstract: Aims and Objectives: This article reports on diet variability in the Dogon Country (Mali) through a bio‐archeological study of pre‐Dogon and early Dogon human remains (7th century to 19th century AD) from collective burial caves in the Bandiagara Escarpment. Materials and Methods: Two hundred and twenty crania from collections curated in Leiden, Paris, and Bamako were studied for dental diseases. In a subset of teeth ( n = 175), δ 13 C and δ 15 N were measured in bulk dentine samples. Results: δ 13 C and δ 15 N values vary widely (−15.4 to −6.0‰ for δ 13 C, 6.0–14.8‰ for δ 15 N, n = 175), and indicate diets dominated by C4 ‐based foods with a focus on plants; animal products played a minor role. There are significant differences between the δ 13 C values from older (pre‐Dogon) and younger (Dogon) periods. Frequencies of caries, antemortem tooth loss, and abscesses increase significantly through time. Individuals from northern caves have more positive δ 13 C and δ 15 N values than southern ones. Discussion and Conclusions: The temporal shifts are probably due to progressive diversification of foods, consistent with archeological evidence showing the addition of rice and vegetables to pearl millet. The geographical disparity is explained by a combination of climatic, environmental, and cultural factors. Last, intersite differences imply that different communities (or subsections thereof) disposed of their dead in different caves. Based on a large sample extending over a wider area and longer time frame than previous work, our study shows that diets in the Dogon Country were neither uniform nor continuous through time, as previously proposed. Our results attest to a complex history of settlement and foodways.